2017
DOI: 10.1002/advs.201700341
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization of Carrier Concentration and Alloy Scattering for Ultrahigh Performance GeTe Thermoelectrics

Abstract: In order to locate the optimal carrier concentrations for peaking the thermoelectric performance in p‐type group IV monotellurides, existing efforts focus on aliovalent doping, either to increase (in PbTe) or to decrease (in SnTe and GeTe) the hole concentration. The limited solubility of aliovalent dopants usually introduces insufficient phonon scattering for thermoelectric performance maximization. With a decrease in the size of cation, the concentration of holes, induced by cation vacancies in intrinsic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
176
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(193 citation statements)
references
References 74 publications
7
176
0
1
Order By: Relevance
“…Indeed, it is found that the Hall carrier concentration ( n H ) linearly decreases from ~7 × 10 20 to ~2 × 10 20 /cm 3 with increasing x (Figure A), which can be roughly understood by the increased mean size of cations by PbTe alloying because of a decrease upon Pb/Sn substitution of the equilibrium cation vacancy concentration . Similar cation‐sized effect on carrier concentration has been found in GeTe thermoelectrics …”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Indeed, it is found that the Hall carrier concentration ( n H ) linearly decreases from ~7 × 10 20 to ~2 × 10 20 /cm 3 with increasing x (Figure A), which can be roughly understood by the increased mean size of cations by PbTe alloying because of a decrease upon Pb/Sn substitution of the equilibrium cation vacancy concentration . Similar cation‐sized effect on carrier concentration has been found in GeTe thermoelectrics …”
Section: Resultssupporting
confidence: 66%
“…As the increase in mean size of cations accompanies with a reduction of carrier concentration in IV‐VI thermoelectrics, a reduction of carrier concentration is expected in Sn 0.8‐ x Mn 0.2 Pb x Te with increasing x . Indeed, it is found that the Hall carrier concentration ( n H ) linearly decreases from ~7 × 10 20 to ~2 × 10 20 /cm 3 with increasing x (Figure A), which can be roughly understood by the increased mean size of cations by PbTe alloying because of a decrease upon Pb/Sn substitution of the equilibrium cation vacancy concentration .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[109] Extending their range of applications further, PCMs are also rapidly garnering interest as candidate materials for photonic devices such as switchable displays (Figure 3b) [110][111][112] or thermoelectrics for waste heat recovery (e.g., by alloying GeTe with guest atoms to modify the atomic and electronic structure). [113][114][115] Adv. Mater.…”
Section: Structure Dynamics and Function In Phase-change Materialsmentioning
confidence: 99%